Pastorale sorg aan beswaardes en ongeduldiges met die oog op die opbou van die gemeente - Rossouw, P. J. (Verbum et ecclesia, 1991)
Pastoral care for the objectors and the impatient: a church growth perspective The aim of this article is to develop a pastoral theological perspective to a recent pastoral problem. This problem is the growing polarization within churches (with the focus on the Dutch Reformed Church) in South Africa today due to theological, church policy, social, economical and political factors. These factors are outlined and analysed systematically. Special attention is paid to the two poles - the objectors and the impatient. The "objector" is described as the church member who experiences an increasing concern and impasse with the church regarding new directions that are followed, and which are not correct according to his convictions and perceptions. The "impatient" is described as a church member who experiences an Increasing impasse with the church because according to him the church is not going far enough in concretizing the full consequences of church policy (as spelled out in Church and Society for example). The nature, symptoms and needs of both are examined and guidelines for a directed pastoral care are proposed.